Proposal of channel estimation method for wireless two-way relay system of using SFBC MIMO-OFDM technique - Mata, Tanairat; Boonsrimuang, Pisit; Mori, Kazuo; Kobayashi, Hideo (My University, 2016)
In a two-way relay communication system, two user terminals (UTs) can communicate and exchange their information data through a relay station by using two timeslots. To realize the two-way relay communication system, each UT is required to estimate channel frequency responses (CFRs) both for up and down links in two timeslots efficiently which be employed in the demodulation of the other user’s information data with frequency domain equalization. To satisfy this requirement, this paper proposes a novel CFR estimation method for the wireless two-way relay communication system of using SFBC MIMO-OFDM technique. The salient feature of proposed CFR estimation method is to employ the maximum likelihood estimation method for the proposed scattered pilot subcarriers assignment which can achieve higher CFR estimation accuracy even in higher time-varying fading channel and when the transmission OFDM signal is sampled by the non-Nyquist rate. In the proposed system, the SFBC technique is also employed for the data subcarriers both for the pilot symbols including data subcarriers and data symbols consisting of all data subcarriers in the frequency axis to improve the bit error rate (BER) performance in the two-way relay system. From the computer simulation results, this paper demonstrates the effectiveness of proposed two-way relay communication system of using SFBC MIMO-OFDM technique. To demonstrate the effectiveness of proposed two-way relay communication system of using SFBC MIMO-OFDM technique, this paper conducts various computer simulations as comparing with the conventional methods in higher time-varying fading channel. From the computer simulation results, this paper confirms that the proposed method even at the non-Nyquist rate can achieve higher channel estimation accuracy evaluated by the normalized mean square error (NMSE) and better BER performances by 5 and 22 times, respectively as comparing with the conventional methods when the normalized Doppler frequency (fdTS) is 10 - 2 and the carrier to noise power ratio (C/N) is 25 dB.
Keywords: Channel estimation; MIMO-OFDM; Non-Nyquist sample rate; SFBC; Two-way relay communication